Bernadette Brady, Astrology: A Place in Chaos - York, Michael (Journal for the study of religion, nature and culture, 2007)
Bernadette Brady, Astrology: A Place in Chaos (Bournemouth: Wessex Astrologer, 2006), 178pp. ISBN 1902405218.